STRUCTURAL AMBIGUITY ON BBC NEWS INSTAGRAM POST - Elma Solihati; Dadan Rusmana; Erlan Aditya Ardiansyah (Journal of English Language Learning, 2022)
The arrangement of words in a grammatically correct sentence can sometimes still lead to multiple interpretations. BBC News, in its Instagram posts, contains sentences that are structurally ambiguous. Therefore, this study aims to find out types of structural ambiguity on BBC News’ Instagram posts that are published from February 2021 until July 2022 and the interpretations arise from those ambiguities. This study uses qualitative method with document analysis technique. The analysis is done by some steps: investigating which word or phrase that makes the sentences become ambiguous, categorizing the ambiguities to their each types, finding out meanings that are produced by those ambiguities, parsing the sentences by using tree diagram, and interpreting the actual meaning of the news headlines or sentences by relating it to the context. The result shows that there are fifty posts from BBC News that contain sentences which are structurally ambiguous. Using theory of Hirst, those ambiguities are categorized as attachment and analytical ambiguity. The ambiguities are mostly caused by phrases that are unclear what their functions are in a sentence. From the result, it can be seen that structural ambiguity is a language phenomenon that is still widely found in our surrounding, not to mention the news headlines. Keywords: structural ambiguity; BBC News; Instagram; headline; sentence